Self-assembled vesicle and rod-like aggregates of functionalized perylene diimide: reaction-based near-IR intracellular fluorescent probe for selective detection of palladium. Issue 21 (5th May 2016) - Singh, Prabhpreet; Mittal, Lalit Singh; Vanita, Vanita; Kumar, Kapil; Walia, Amandeep; Bhargava, Gaurav; Kumar, Subodh
Abstract : Aggregates ofPS-PDI after Pd 0 based depropargylation show de-aggregation and near-IR, ratiometric absorbance changes in water and live HeLa cells. Abstract : Herein, we report design, synthesis, and self-assembly of perylene diimide (PDI) based near-IR intracellular probe (PS-PDI ).PS-PDI molecules undergo aggregation to form self-assembled nanospheres and nanorods morphology in THF : H2 O (1 : 1) and DMSO : H2 O (1 : 9), respectively. The nanospheres have an open hole on surface reminiscent of vesicle structure (with a diameter of internal void in the range of 20–25 nm) whereas lengths of the nanorods extended up to few μm range. The Pd 0 based depropargylation leads to de-aggregation of thesePS-PDI aggregates into smaller spherical aggregates as evidenced by DLS, SEM, and TEM studies. Interestingly, these aggregates ofPS-PDI in solution show highly sensitive behavior in the presence of Pd 0 showing absorbance changes in NIR region ( λ max = 710 nm) and quenching of emission at λ em 630 nm (DMSO : H2 O, 1 : 9) with a limit of detection = 6.6 × 10 −9 M or at λ em 564 nm (THF : H2 O, 1 : 1) with limit of detection = 2.1 × 10 −8 M. Time and concentration dependent kinetics profiles ofPS-PDI aggregates revealed an impressive rate constant value of 0.4 s −1 and 0.21 s −1 (DMSO : H2 O, 1 : 9), respectively in fluorescence and UV-Vis spectroscopy using 2 × 10 −5 M concentration of Pd 0 .PS-PDI undergoes rapid internalization into HeLa cells with low cytotoxicity and was successfully used as an intracellular imaging reagent for Pd 0 in live HeLa cells. For practical applications, we exploited these nano-aggregates ofPS-PDI for estimation of Pd 2+ in the presence of a NaBH4 –PPh3 mixture, Pd 0 in drug and environmental samples, and Pd 2+ in urine samples with excellent selectivity and sensitivity.